Bias Atensi sebagai Moderator pada Hubungan antara Afek Positif dan Kebahagiaan di Populasi Remaja - Nurlyta Candra Dewi; Eko Handayani (INSAN Jurnal Psikologi dan Kesehatan Mental, 2023)
Previous research has shown a significant correlation between positive affect and happiness. However, previous studies have used more conscious measures, while positive affect influences cognitive function through unconscious processes. This study proposes attentional bias as an unconscious process that is assumed to moderate the correlation between positive affect and happiness, especially in the adolescent population. This study used a correlational design with the total participants of 87 high school students (M = 16.5 years). Three measurements were used; Subjective Happiness Scale for Happiness, Positive and Negative Affect Schedule for positive affect, and Emotional Stroop Task for attentional bias. The results of the moderating analysis using Jamovi showed that attentional bias on word stimulus related to happiness and threat was significantly moderated the correlation between positive affect and happiness. The results of this study can be used as a reference for designing interventions on attentional bias in the adolescent population.